AUDIT SISTEM MANAJEMEN LINGKUNGAN RUMAH SAKIT - Paramita, Pradnya (Jurnal Akuntansi AKUNESA, 2014)
Hospitals in the health sector as a means of organizing health services is one source of toxic waste processing to get a good start of the reduction, container, collection, temporary storage, transport and processing at the source. The purpose of this study is to describe the steps in auditing environmental management system and examples of its application. In this research, descriptive research method of evaluation and analysis of the data processed by qualitative techniques to describe management efforts toxic waste Hospital. The results showed introduce environmental management system audits and provide advice on steps that need to be done in auditing environmental management systems.KEYWORDS:Environmental Management System, Audit EMS, Toxic Waste.